2014
DOI: 10.1073/pnas.1407777111
|View full text |Cite
|
Sign up to set email alerts
|

Two miRNA clusters, miR-34b/c and miR-449 , are essential for normal brain development, motile ciliogenesis, and spermatogenesis

Abstract: Two miRNA clusters, miR-34b/c and miR-449, are essential for normal brain development, motile ciliogenesis, and spermatogenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
259
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(280 citation statements)
references
References 31 publications
15
259
0
Order By: Relevance
“…These findings suggest that miRNAs necessary to confer spermatogonial differentiation may be synthesized by non-canonical enzymes, and the underlying mechanism remains to be elucidated. It has recently been found that miR-449 is predominantly expressed in mouse testes and it is mainly located in spermatocytes and spermatids (Bao et al 2012, Wu et al 2014. Interestingly, miR-34b and miR-34c have been found to resemble the 'seed' sequence of miR-449.…”
Section: Functions Of Mirnas In Meiosis and Spermiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that miRNAs necessary to confer spermatogonial differentiation may be synthesized by non-canonical enzymes, and the underlying mechanism remains to be elucidated. It has recently been found that miR-449 is predominantly expressed in mouse testes and it is mainly located in spermatocytes and spermatids (Bao et al 2012, Wu et al 2014. Interestingly, miR-34b and miR-34c have been found to resemble the 'seed' sequence of miR-449.…”
Section: Functions Of Mirnas In Meiosis and Spermiogenesismentioning
confidence: 99%
“…Interestingly, miR-34b and miR-34c have been found to resemble the 'seed' sequence of miR-449. Coincidentally, miR-34b and miR-34c exhibit a similar effect to that of miR-449 during the development of male germ cells and spermatogenesis (Bouhallier et al 2010, Bao et al 2012, Wu et al 2014. Individual deficiency in miR-34b/c or miR-449 appears to have no obvious effect; however, simultaneous inactivation of miR-34b/34c and miR-449 leads to mouse oligoasthenoteratozoospermia (Wu et al 2014), implicating that double or triple knockout approach of miRNAs is needed to obtain the phenotype for certain miRNAs.…”
Section: Functions Of Mirnas In Meiosis and Spermiogenesismentioning
confidence: 99%
“…The target miRNAs, miR-34b-5p and miR-449a in the testis, which were associated with spermatogenesis or EGME induced-testicular toxicity (Fukushima et al, 2011;LizĂ© et al, 2011;Smorag et al, 2012;Wu et al, 2014), were applied to RT-qPCR with 7900HT Fast Real Time PCR System (Applied Biosystems). The primers for miR-34b-5p and miR-449a (Assay IDs: #000427 and 001030) were designed based on each respective human sequence obtained from miRBase (http://microrna.sanger.…”
Section: Reverse Transcription-quantitative Real-time Pcr (Rt-qpcr) Amentioning
confidence: 99%
“…Conditional knockout mice that lack dicer, a prerequisite for the production of miRNA, in Sertoli cells are infertile, suggesting the importance of miRNAs on spermatogenesis (Papaioannou et al, 2009). Additionally, several miRNAs such as miR-34b-5p and miR-449a that are preferentially expressed in the testis are assumed to have an intimate involvement in germ cell development (Fukushima et al, 2011;Wu et al, 2014). Indeed, double KO mice with miR-34b/c and miR-449 deficiency had severely disrupted spermatogenesis (Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation